Interactive media training in improving student learning outcomes - Natsir, Taufiq; Rasyid, Ramli; Ishak, Ishak; Ridwan, Ridwan; Haedar, Ahmad Wahidiyat (Jurnal Hasil Inovasi Masyarakat, 2025)
Interactive media training is an important need in improving the quality of the learning process in higher education. The use of interactive media allows students to play an active role in the learning process so as to improve understanding and learning outcomes. This community service aims to carry out training on the use of interactive media for lecturers and students and analyze its impact on student learning outcomes. The activity involved 33 students and lecturers of the Faculty of Engineering, State University of Makassar as training participants. The training method is in the form of interactive workshops and hands-on practice of using interactive media. Evaluation is carried out through pre-test and post-test, as well as observation of participant involvement. The results showed a significant increase in student learning outcomes and an improvement in lecturers' skills in applying digital learning media. This training is expected to encourage the implementation of interactive media more optimally in the learning process in higher education.